Factors influencing the pronunciation of adult speakers of a foreign language - Szalkowska-Kim, Emilia (Lingua Posnaniensis, 2014)
The present paper is an overview of selected investigations into acquisition of second language phonology (L2).1 It describes L2 phonology researchers’ attempts to determine the number, quantity, quality and roles of the factors which shape the pronunciation of L2 adult speakers, i.e. what is the influence of native language limitation, how the L2 phonology acquisition is governed by universal linguistic features, and whether adults use the same processes in acquiring the L2 that are used by children when they acquire their first language. This article will describe a number of longstanding phonetic and phonological projects whose aim was to discover patterns in the improvement of pronunciation in a second language (see research by Archibald, Broselow, Eckman, Flege, Hancin-Bhatt, Major and Weinberger, published in numerous compilations). It strives to explain the universal stages in the development of second language phonology. The main goal of the research is to assess the grammatical knowledge of the L2 learner, i.e. their competence in their interlanguage. The analyses show typological disproportions and universality of the strategies applied by the speakers in the target language. A few important hypotheses have been established (see below for their description), but it is important to note that most of the results verifying these hypotheses concern the acquisition of the English language, with a variable being the “input” languages of the speakers. Although this unilateral focus of the research projects reflects the expansion of the English language as the lingua franca of modern times, it might severely limit understanding of the important and interesting aspects of second language acquisition which structurally do not apply to that language, and are consequently overlooked.